2015
DOI: 10.17271/2318847232120151151
|View full text |Cite
|
Sign up to set email alerts
|

Análise Dos Dados Sobre Resíduos Sólidos Nas Bases Da PNSB E Do Snis

Abstract: RESUMOEsta pesquisa visa comparar os dados, sobre resíduos sólidos, obtidos em duas bases de informação vinculadas ao Governo Federal, a Pesquisa Nacional de Saneamento Básico -PNSB (2008) e o Sistema Nacional de Informações sobre o Saneamento -SNIS (2008 e 2013). Essas bases são utilizadas pelo Governo para a edificação de Políticas Públicas, porém possuem periodicidade de aplicação e metodologia diferentes. Para a comparação, foram utilizadas duas variáveis: "Coleta domiciliar de lixo" e "Coleta seletiva". F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Standardization among national institutions in waste management in Brazil is crucial for ensuring the quality and reliability of sustainability indicators. For instance, Pupin et al [80] identified divergences between methodologies regarding waste data collection, highlighting the critical need for uniform criteria across different institutions. Thus, by establishing standardized methods, definitions, and protocols for data collection, public institutions can enhance the consistency, comparability, and accuracy of waste data.…”
Section: Indicators Frameworkmentioning
confidence: 99%
“…Standardization among national institutions in waste management in Brazil is crucial for ensuring the quality and reliability of sustainability indicators. For instance, Pupin et al [80] identified divergences between methodologies regarding waste data collection, highlighting the critical need for uniform criteria across different institutions. Thus, by establishing standardized methods, definitions, and protocols for data collection, public institutions can enhance the consistency, comparability, and accuracy of waste data.…”
Section: Indicators Frameworkmentioning
confidence: 99%
“…According to Pupin et al (2015), Brazilian cities may be suffering financial penalties from the Federal Government if they do not report the sewer data. Therefore, only 64% of the national cities report to SNIS in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar disso, revela uma nova maneira de abordar e expandir o tema do saneamento e saúde: primeiro porque avaliações com tendências históricas possibilita verificar como se desenvolveram os serviços e ações em saneamento e saúde sob uma perspectiva temporal; segundo, pois a abordagem a nível municipal é útil para um melhor entendimento dos resultados de uma determinada política pública, pouco explorada na literatura quando se trata de múltiplas escalas geográficas: municípios, microrregiões, mesorregiões e macrorregiões; e, em terceiro, pela utilização de dados do Sistema Nacional de Informações sobre Saneamento (SNIS), devido os dados do Instituto Brasileiro de Geografia e Estatística (IBGE) serem de 2008, cuja atualização amostral para os indicadores de saneamento se limita à amostras para o Brasil, Regiões, Unidades Federativas e Regiões Metropolitanas, enquanto que o SNIS fornece um panorama do acesso ao saneamento a nível de unidade da federação e município (PUPIN;BRUMATTI;GIANNINI, 2016;FREITAS et al, 2018).…”
Section: Introductionunclassified